Completeness of Shopping Skills Media Features for Students with Mental Retardation at Special Junior High School: A Literature Review - Nindya Ayu Rizqianti; Ediyanto Ediyanto; Mohammad Efendi (Universitas Negeri Malang, 2021)
The students with mental retardation ability in the shopping skills show that students are still not able to do it well. Several factors cause the inability of students with mental retardation in shopping skills, namely: students do not understand the concept of money, are often confused about arithmetic operations on money material, cheap and expensive concepts, and shopping activities. This study uses a systematic literature review method from articles that have been published and a descriptive method that aims to determine the variety of shopping skills media and the completeness of features that must exist in shopping skills media for students with mental retardation. The research results obtained from several studies on shopping skills media for students with mental retardation are relevant. It can be seen that there is still minimal development of shopping skills media. Another result is that using several types of shopping skills learning media can improve the shopping ability of students with mental retardation from the material aspect. From theory to practical aspects, they are iPad-based animated image and video media.